Development of Creative Thinking Skills Instruments based on local wisdom in Ecology Material - Gunaria Siagian; Winarto Silaban (International Journal of Multidisciplinary Sciences and Arts, 2026)
Creative thinking skills emphasize the aspects of fluency, flexibility, originality, and detail. This study aims to develop a local wisdom-based Creative Thinking Skills Instrument on Ecology Material in the Biology Education Study Program of HKBP Nommensen University, Pematangsiantar. The development stage of the local wisdom-based Creative Thinking Skills instrument is needs analysis, the second stage is designing the local wisdom-based Creative Thinking Skills instrument, the third stage is Development. The validity test obtained a score of 44.67 with valid criteria. The results of a limited trial of the local wisdom-based Creative Thinking Skills instrument in biology learning on ecology material showed that there were 7 (35%) questions that had very high validity, 8 (40%) questions had high validity, 4 (20%) questions had sufficient validity, and 1 (5%) had low validity. From the results of the limited trial, the local wisdom-based Creative Thinking Skills instrument in biology learning was very suitable for use in biology learning on ecology material. Furthermore, from the results of a limited trial of the local wisdom-based Creative Thinking Skills instrument, an average score of 0.724 was obtained with valid criteria. Furthermore, the reliability test results of the local wisdom-based creative thinking skills instrument in a limited product trial obtained ? = 0.972, with very high criteria. This indicates that this local wisdom-based creative thinking skills instrument is highly valid and reliable for development in biology learning on ecological material.